Meta-analysis of risk factors for recurrent gestational diabetes mellitus - Yuan Lu; Jianchun Huang; Jian Yan; Qingfang Wei; Meirong He; Chunlan Yuan; Yu Long (BMC Pregnancy and Childbirth)
Abstract Background To comprehensively evaluate the risk factors for recurrent gestational diabetes mellitus (GDM) in women with a history of GDM during re-pregnancy. Methods Articles about risk factors for recurrent GDM were searched in China National Knowledge Infrastructure, Wanfang Data, VIP Database for Chinese Technical Periodicals, PubMed, EMBASE, the Cochrane Library, and Web of Science from the date of establishment to January 2023. Meta-analysis of risk factors for recurrent GDM was performed using STATA/SE 15.1 software. Results A total of 19 studies were included in the meta-analysis, comprising 15 case-control studies and 4 cohort studies, involving 11,385 patients. Among them, 2,462 patients experienced recurrent GDM, while 2,909 did not. The analysis of case-control studies revealed a GDM recurrence rate of 48%. Meta-analysis identified several significant risk factors for GDM recurrence: advanced maternal age at subsequent pregnancy [ES = 3.02, 95% CI (1.24,2.79), P = 0.003], increased BMI prior to the subsequent pregnancy [ES = 2.23, 95% CI (1.04,1.72), P = 0.026], elevated 1-hour plasma glucose levels in oral glucose tolerance test (OGTT) during previous pregnancy [ES = 2.79, 95% CI (1.11,1.78), P = 0.005], increased 2-hour OGTT glucose levels in previous pregnancy [ES = 2.75, 95% CI (1.11,1.91), P = 0.006], and previous delivery of macrosomia [ES = 3.48, 95% CI (1.38,3.18), P = 0.001]. All these factors showed statistically significant differences between the recurrence and non-recurrence groups. Pregnant women with a history of GDM can reduce the risk of recurrence by adopting a reasonable pregnancy plan, such as avoiding advanced maternal age, managing body weight, controlling blood glucose levels during pregnancy, and losing weight before conception. Conclusion Advanced maternal age, elevated BMI before subsequent pregnancy, increased OGTT levels during the previous pregnancy, and the delivery of macrosomia are significant risk factors for recurrent GDM.